Using microtremor data to obtain dynamic properties of soils in the Veracruz-Boca del Rio metropolitan areaMendeley Data - José E. Barradas-Hernández; Sergio Márquez-Domínguez; Franco Antonio Carpio-Santamaria; Alejandro Vargas-Colorado; Abigail Zamora-Hernández; Roberto Rivera-Baizabal (Data in Brief)
The data presented here are the result of microtremor measurements at 44 points in three different soil types classified according to their fundamental vibration frequencies, on the metropolitan area of Veracruz-Boca del Río, Mexico. These Data are raw and was obtained using a GÜRALP 6TD model broadband orthogonal triaxial seismometer with an integrated 24-bit digitizer with a minimum recording time of 30 min and a recording rate of 100 samples per second (sps). The microtremor records were used to construct the H/V spectral ratios using the method of Nakamura. These H/V spectral ratios are a good approximation of the transfer function between the vibration waves in the sediment and the rigid stratum. Therefore, they can be used to construct seismic microzonation maps, seismic intensity maps and spectra for designing seismic resistant structures. One-dimensional stratigraphic soil models were obtained by processing the H/V spectral ratios. The relevant data from these models are layer thickness, primary wave velocities (Vp), secondary wave velocities (Vs) and density. These models represent a mathematical approximation of the soil structure that can be used to dynamically classify it according to Mexican technical codes.